Design of a Learning Analytics framework proposal in academic contexts - Cirulli, Federica; Caporarello, Leonardo; Milani, Manuela (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
In the last decades, learning analytics (LA) have been considered as one of the key emerging trend in higher education (Vassakis et al., 2018) and they have attracted a lot of attention among researchers and designers for their potential to address some of the major challenges in the academic sector (Bach, 2010). Despite the broad interest and implementation of LA processes, there remain numerous issues regarding the availability of developed and adaptable-to-the-context reference framework across Universities (Gaševi et al., 2015). Furthermore, scholars and practitioners have approached LA from a range of perspectives: it is necessary to define not only the aims of what could be achieved using LA but also what should be done to attain it. Generally, LA are considered as measurement, collection, analysis and reporting of learners’ data and their contexts, to optimize learning and the environments in which it occurs (Khalil and Ebner, 2016). Starting from this definition, and using an action research method, we propose an “extended” LA framework that puts learner and instructor at the centre of it.